Utilization of Functional Local Foods in Anemia Prevention: Collaboration with MAHSA University - Arifah Septiane; Zahrah Saad; Siti Rohmah; Didih Faridah; Deassy Ratna Juwita Sari; Salpa Nurpadilah; Dewi Fitriani; Mahmudatun Ni’mah (PT Inovasi Pratama Internasional, 2026)
Anemia remains a significant public health problem, particularly among adolescent girls and women of reproductive age, due to its adverse effects on health, productivity, and quality of life. One potential strategy for anemia prevention is the utilization of functional local foods that are rich in iron and other nutrients essential for hemoglobin formation. This community service program, entitled “Empowerment of Midwifery Students through the Utilization of Functional Local Foods in Anemia Prevention: Collaboration with MAHSA University,” aimed to enhance the knowledge and capacity of midwifery students regarding the use of functional local foods as a sustainable approach to anemia prevention. The program was implemented through a collaborative partnership between Universitas Galuh, Indonesia, and MAHSA University, Malaysia. The activities were conducted through three main stages: program socialization, implementation, and monitoring and evaluation. The socialization stage focused on introducing the program objectives, benefits, and implementation strategies to participants and stakeholders. . A total of 40 participants were involved in the program, consisting of 36 midwifery students from Indonesia and 4 students from Malaysia. Educational materials focused on anemia prevention, the nutritional benefits of local food resources, and the utilization of functional local foods such as moringa leaves, spinach, legumes, and other locally available food sources. The results demonstrated an improvement in participants’ knowledge, understanding, and awareness regarding anemia prevention through the utilization of functional local foods. Participants also showed enhanced abilities in identifying nutritious local food resources and delivering health promotion messages to the community.In conclusion, the program successfully enhanced students’ capacity as future healthcare professionals and health promotion agents while promoting the sustainable utilization of local food resources for anemia prevention. This program may serve as a model for community empowerment initiatives that integrate health education, local resource utilization, and international collaboration to improve public health outcomes.